Development of an HPLC method for the radiochemical purity evaluation of [18F]fluoroestradiol (Brazilian Journal of Radiation Sciences (BJRS), 2019)
18F-Fluoroestradiol ([18F]FES), an estrogen analog, is a radiopharmaceutical used in Positron Emission Tomography (PET) that allows evaluating the tumor cell receptor profile and the best therapy strategy, the staging, the prognosis and the response to therapy in several breast cancer cases. As there is not any pharmacopoeia’s monograph of [18F]FES to standardize its quality control criteria, this work presents a new HPLC’s method to perform the [18F]FES radiochemical purity. A liquid chromatograph was used with radioactivity and ultraviolet detectors. Three concentrations of fluoroestradiol standard solution were used along the test. Their retention time was compared to its relative radiolabelled analogue to confirm its identity. Several mobile phases with acetonitrile and two mobile phase flows were tested to optimize the runs. Peaks symmetry, retention time, theoretical plates and resolution were analyzed to choose the best conditions. The mean retention time of both standard Fluoroestradiol and [18F]FES solutions were the same, demonstrating that [18F]FES formulation did not interfere with [18F]FES analysis. The best conditions were 1.2 mL/min and isocratic 40% V/V acetonitrile in water, which gave [18F]FES peak resolution greater than 6 and symmetry factor of 1. Thus, the developed method is ready to be validated and implemented in [18F]FES quality control routine in CDTN/Brazil.